2013
DOI: 10.5688/ajpe776116
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Dual PharmD/MPH Programs Offered at US Colleges and Schools of Pharmacy

Abstract: Objective. To assess the prevalence and characteristics of curriculum in dual doctor of pharmacy (PharmD)/master of public health (MPH) degree programs offered by US pharmacy programs.Methods. An 18-item survey instrument was developed and distributed online to faculty members at US colleges and schools of pharmacy. Results. Of the 110 colleges and schools that responded, 23 (21%) offered a PharmD/MPH degree. Common characteristics of these 23 programs included current PharmD program structure (3 1 1 year), ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Some regions in North Dakota contract with workmen’s compensation programs for pharmacists to provide pain management counseling 40,41. Formal public health programs, such as the dual degree PharmD/MPH program at North Dakota State University, create the opportunity for increased training in the delivery of public health services 42. Gortney and colleagues reported on the prevalence of PharmD/MPH dual degree programs nationwide, and this report suggested that more pharmacy students are pursuing and have additional exposure to public health than in traditional pharmacy programs 42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some regions in North Dakota contract with workmen’s compensation programs for pharmacists to provide pain management counseling 40,41. Formal public health programs, such as the dual degree PharmD/MPH program at North Dakota State University, create the opportunity for increased training in the delivery of public health services 42. Gortney and colleagues reported on the prevalence of PharmD/MPH dual degree programs nationwide, and this report suggested that more pharmacy students are pursuing and have additional exposure to public health than in traditional pharmacy programs 42.…”
Section: Discussionmentioning
confidence: 99%
“…Formal public health programs, such as the dual degree PharmD/MPH program at North Dakota State University, create the opportunity for increased training in the delivery of public health services 42. Gortney and colleagues reported on the prevalence of PharmD/MPH dual degree programs nationwide, and this report suggested that more pharmacy students are pursuing and have additional exposure to public health than in traditional pharmacy programs 42. Public health education has been enhanced in colleges/schools of pharmacy, in accordance with CAPE Outcomes, and should result in greater exposure in both didactic and experiential pharmacy student training 43.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Shannon et al reported that among the 120 accredited colleges and schools of pharmacy in 2011, forty-three percent offered dual degree programs including the PharmD/MPH degree 11. A recent analysis of the prevalance and characteristics of PharmD/MPH dual degree programs in the United States conducted by Gortney et al revealed that twenty-one percent of the 110 schools of pharmacy responding to the survey reported having a combined PharmD/MPH dual degree program 12. Fourteen of the twenty three schools offering PharmD/MPH dual degrees reported having one to ten pharmacy students enrolled, four reported having eleven to twenty students enrolled 12.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the prevalance and characteristics of PharmD/MPH dual degree programs in the United States conducted by Gortney et al revealed that twenty-one percent of the 110 schools of pharmacy responding to the survey reported having a combined PharmD/MPH dual degree program 12. Fourteen of the twenty three schools offering PharmD/MPH dual degrees reported having one to ten pharmacy students enrolled, four reported having eleven to twenty students enrolled 12. Of note, approximately seventy percent of the colleges and schools offering dual degrees had been in existence for less than six years and one third were in their first year of existence 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation